Organizational Responsibility Management Based On A Framework - Saputra, Andika (Mutiara: Multidiciplinary Scientifict Journal, 2024)
The purpose of this article is to outline the structure of management obligations and liabilities. An approach to conducting a literature review that was taken from management and organizational textbooks was used to prepare the essay. A framework is a plan, structure, guiding idea, or idea of how something will be done. So, there must be a framework for what the organization will do in order for it to exist. A system in which people are interconnected or tied to one another and develop networks that benefit one another is called an organization. Management operates inside an organizational structure. In other words, when the management process is in motion, the organization serves as a container, forum, or functional group. For management and its members, an organization functions as a road map for achieving objectives. The organization is a place where a collection of individuals is led to accomplish particular goals from the organization because the organization is a complicated management art that incorporates humans who are intended to fulfill predetermined goals.